2012
DOI: 10.1590/s0102-37722012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Vitalidade Subjetiva - EVS: evidências de sua adequação psicométrica

Abstract: Subjective Vitality Scale -SVS: Evidences of its Psychometric AdequacyABSTRACT -This paper presents empirical evidence of the psychometric adequacy of the Subjective Vitality Scale (SVS), based on three studies. In Study 1, 200 undergraduate students responded the SVS. The SVS showed a unidimensional factor structure (a = .73). In Study 2, another 200 undergraduate students answered the same instrument. A confirmatory factor analysis (CFA) confirmed the factor structure of Study 1, although item 2 was inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
9
0
6
Order By: Relevance
“…Although instruments exist in Brazil which measure positive behaviors (Gouveia et al, 2005(Gouveia et al, , 2012, no measure was found which dealt specifically with positivity as a tendency for people to act positively regarding their own lives. As a result, this undertaking is considered relevant, as it offers evidence of a psychometrically-adequate measure for use in research and even in the clinical ambit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although instruments exist in Brazil which measure positive behaviors (Gouveia et al, 2005(Gouveia et al, , 2012, no measure was found which dealt specifically with positivity as a tendency for people to act positively regarding their own lives. As a result, this undertaking is considered relevant, as it offers evidence of a psychometrically-adequate measure for use in research and even in the clinical ambit.…”
Section: Discussionmentioning
confidence: 99%
“…This measure was originally proposed by Ryan and Frederick (1997), with a version made up of seven items; later improved by Bostic, Rubio and Hood (2000), who proposed a more parsimonious version of six items. This version was adapted to the Brazilian context by Gouveia et al (2012), producing a strategy which brought together the six items (e.g., "I feel alive and vital"), answered on a seven-point scale varying from 1 (Not at all true) to 7 (Very true). It is a one-factor measure, with a Cronbach's alpha superior to .70 for its Brazilian adaptation.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify the assumptions of concurrent validity of SVS, a correlation analysis was performed through the Pearson coefficient r, between subjective vitality and satisfaction with life. As the subjective vitality construct reflects well-being 4 , it is likely that it has strong and positive correlations with other well-being variables (satisfaction with life) 24 . Finally, in order to analyze the possible differences in subjective vitality between active and sedentary subjects of our sample, the t-Student test was used, which allows studying how the means of two populations are significantly different 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Esta tendência compactua com a própria definição de saúde da Organização Mundial de Saúde [World Health Organization, WHO], que a caracteriza como um estado completo de bem-estar físico, mental e social, e não a mera ausência de doença (WHO, 2013). O otimismo -tendência relativamente estável para a criação de expectativas (Blackwell et al, 2013), a vitalidade -nível de vigor físico, mental e estado de alerta do indivíduo (Gouveia et al, 2012) e o funcionamento laboral são conceitos que, embora distintos, surgem muitas vezes associados entre si. Diversos estudos sugerem que a presença de vitalidade/otimismo promove, não só estados de saúde física e psicológica (Boehm, Peterson, Kivimaki, & Kubzansky, 2011;Clanton et al, 2011;Griggs et al, 2007;van Fenema et al, 2012), mas também níveis superiores de funcionamento laboral (Patel et al, 2010).…”
unclassified